Indium tin oxide (ITO) and reduced graphene oxide/indium tin oxide (rGO/ITO) thin films: effect of synthesis parameters on ozone gas detection - Hernandez, Laureano Javier Ensuncho (2021)
Nowadays, continuous attempts are being employed to obtain gas sensors materials with high sensitivity, fast response, good selectivity, and low detection limits. Resistive-based gas sensors based on semiconductor metal oxides (SMOs) are most widely used for gas detection applications. However, their poor selectivity and high operating temperature have given rise to the need to implement several strategies to overcome these drawbacks and, at the same time, reach enhanced sensitivity. Among them, binary, ternary metal oxides, variations in synthesis conditions, and implementing SMOs with other materials, such as reduced graphene oxide (rGO) have been explored. In this context, the gas sensing properties towards ozone gas of Indium Tin Oxide (ITO) thin films obtained by frequency-sputtering method was evaluated. ITO, which is composed of indium oxide (In2O3) and tin oxide (SnO2)), was deposited under different deposition conditions (ex- and in- situ thermal annealing) and sputtering atmosphere (Ar or Ar+O2), as well as the formation of a rGO/ITO thin film was explored. The results show that the sample heat-treated ex-situ at 300°C presents the best response to ozone gas under the same working temperature and ozone amount. Its optimal operating temperature and thin film thickness towards ozone detection was 300°C and 100 nm, respectively. The film deposited in the argon atmosphere (Ar-film) shows a higher ozone response than that deposited in an argon and oxygen mixing atmosphere (Ar+O2). The rGO/ITO thin film deposited in the Ar atmosphere does not display a larger difference in the response in relation to the ITO film deposited on Ar atmosphere. On the other hand, the rGO/ITO thin films deposited in the Ar and O2 atmospheres (rGO/Ar+O2) exhibit a higher response regarding the ITO film deposited in Ar+O2 atmosphere on the same conditions. Moreover, the ozone sensing response of the rGO/ITO thin film deposited on Ar+O2 atmosphere presents a better response when operating at 200°C. At 200°C, its response is approximately three times compared when measured at 300°C.